Energía solar en espacios públicos - Acedo Chuquipiondo, Ricardo Javier (2021)
This project seeks to relieve the sustainability problem that part of the electricity generation system in Peru suffers, using trends, information, technology and available resources, for their incorporation in public areas such as parks being this transformation a showcase that promotes awareness of the society for the care of the environment. The methodology used, to validate the hypotheses resulting from this project, allows a first proposal to be presented being the same iteratively validated, giving the team direct feedback from users and end customer until obtaining a minimum viable product that fits to identified needs. Based on this result, it is possible to carry out financial projections that allow us to make the venture viable, reflecting in this model the real market conditions, adopting a conservative position, considering the risks of the economic environment in a comprehensive manner. Finally, the results obtained have been the product of real information collected in person and virtually, the latter due to the restrictions of the State of Emergency decreed in Peru since March, 2020 due to the pandemic caused by COVID-19. However, it is concluded that the valuation of the project is high, as well as its scalability potential when addressing global problems and local needs in the same deliverable.